2022
DOI: 10.14715/cmb/2021.67.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptides from Allium subhirsitum L. extracts: Pharmacokinetics properties, toxicity prediction and in silico study against SARS-CoV-2 enzymes and pro-inflammatory proteins

Abstract: Developing new prophylactic and therapeutic agents with broad-spectrum antiviral activities is urgently needed to combat emerging human severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since no available clinically antiviral drugs have been approved to eradicate COVID-19 as of the writing of this report, this study aimed to investigate bioactive short peptides from Allium subhirsutum L. (Hairy garlic) extracts identified through HR-LC/MS analysis that could potentially hinder the multiplication cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Therefore, we may overestimate or underestimate the coverage. In relation to Covid-19, many studies have been conducted on its cause, prevention, diagnosis, prevalence, and other issues that need attention (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Differences In Frail Components In Older Adults With Vaccine...mentioning
confidence: 99%
“…Therefore, we may overestimate or underestimate the coverage. In relation to Covid-19, many studies have been conducted on its cause, prevention, diagnosis, prevalence, and other issues that need attention (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Differences In Frail Components In Older Adults With Vaccine...mentioning
confidence: 99%
“…In a study, Snoussi et al. (2021) used Allium subhirsutum L. extracts to inhibit furin protein and found that the top peptides against furin protein were Thr–Leu–Trp (−9.6 kcal/mol) and Gln–Phe–Tyr (−9.4 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“…However, some laboratory studies have shown the effect of garlic in the inhibition of SARS-CoV-2 replication [ 30 - 34 ]. In our study, garlic extract was combined with bovine colostrum and other herbal ingredients.…”
Section: Discussionmentioning
confidence: 99%